PERAN GAYA KEPEMIMPINAN DEMOKRATIS DAN KARAKTERISTIK INDIVIDU TERHADAP PENGEMBANGAN KARIR PEGAWAI DENGAN FASILITAS KERJA SEBAGAI VARIABEL INTERVENING PADA KANTOR LURAH DI KECAMATAN LONG MESANGAT KUTAI TIMUR - Ria Fitria Rachimah (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2026)
This study aims to analyze the influence of democratic leadership style and individual characteristics on employees’ career development, as well as to examine the role of work facilities as an intervening variable. The research was conducted at the Village Head Office of Long Mesangat District, East Kutai Regency, using a quantitative survey approach. A total of 162 employees were selected through purposive sampling. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The findings reveal that democratic leadership style and individual characteristics do not have a significant effect on either work facilities or employees’ career development. In contrast, work facilities were found to have a positive and significant influence on career development. Furthermore, work facilities do not serve as a mediating variable in the relationship between the independent variables and career development. This finding may be attributed to the highly structured and centrally regulated nature of the government personnel system, which limits the direct influence of individual factors and leadership practices on employees’ career advancement.